2020
DOI: 10.52716/jprs.v10i2.352
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of carbon steel in formic acid as an organic pollutant under the influence of concentration cell

Abstract: The presence of contaminants in water even in small amounts can cause considerablecorrosion damages of metals. This is due to free corrosion effect or the formation ofconcentration cell of pollutants resulting in a galvanic effect. The current work was devotedto study the effect of formic acid (CH2O2) as an organic pollutant on the corrosion rate ofcarbon steel under different operating conditions. It includes an investigation of galvaniccorrosion caused by the establishment of concentration cell of formic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…It is also directly proportional to the increase in the carbon steel corrosion rate, as illustrated in Table 3. This is in accordance with what numerous researchers have observed [19,20]. From Figures (8) and ( 9) and Tables ( 4) and ( 5), it can be seen that the inhibitor concentration of both the sodium nitrate and castor oil is inversely proportional to the carbon steel corrosion rate, given that the higher the inhibitor concentration, the lower the corrosion rate and vice versa.…”
Section: Effect Of Temperature and Rotational Velocity On Dissolution...supporting
confidence: 91%
“…It is also directly proportional to the increase in the carbon steel corrosion rate, as illustrated in Table 3. This is in accordance with what numerous researchers have observed [19,20]. From Figures (8) and ( 9) and Tables ( 4) and ( 5), it can be seen that the inhibitor concentration of both the sodium nitrate and castor oil is inversely proportional to the carbon steel corrosion rate, given that the higher the inhibitor concentration, the lower the corrosion rate and vice versa.…”
Section: Effect Of Temperature and Rotational Velocity On Dissolution...supporting
confidence: 91%
“…This is caused by the rise of the oxygen transferred on the surface of c-steel, being a main factor for corrosion. These results are almost similar to conclusions of previous students [19]. From Figures (5) to (8) and Table ( 4), it can be observed that the inhibitors concentration of castor oil, flaxseed oil, sunflower oil and corn oil is inversely proportional to the corrosion rate of c-steel, where the corrosion rate of metal increases as concentration of the inhibitor decreases and vice versa.…”
Section: Effect Of Rotational Speed On Corrosion Rate Of C-steel and ...supporting
confidence: 89%
“…Both Table (3) and Figure (3) confirm that the corrosion rate of c-steel increases with the increasing of rotational speed, and this occurs because of the removal of the protective surface films due to the high flow of velocity, leading to an increase in the diffusion of oxygen on the metal surface, causing meanwhile a decrease in the boundary and diffusion layers [19].…”
Section: Effect Of Rotational Speed On Corrosion Rate Of C-steel and ...mentioning
confidence: 73%
“…Biofouling leading to clog and operation failure are one of the severe challenges underwater components are facing today. Macrobiotic reproduction changes the local micro-environment and the surface state of the albronze components, and subsequently accelerates the corrosion at the metal/water interface [5,6]. Establishing a barrier against biofouling for underwater facilities is hence of great significance.…”
Section: Introductionmentioning
confidence: 99%